O genero Miconia Ruiz & Pav. (Melastomataceae) : I. Listagens analiticas, II. Revisão taxonomica da seção hypoxanthus (Rich. ex DC.) Hook.f. - Goldenberg, Renato, 1968- (2000)
Orientador: Angela Borges Martins